Pengembangan Aplikasi Sistem Informasi Pelatihan Pegawai Berbasis Website Pada PT Inacon Luhur Pertiwi Jakarta - Handa Gustiawan; Muhammad Ridwan Effendi (Jurnal Teknik dan Science, 2025)
This study aims to develop a web-based employee training information system application at PT Inacon Luhur Pertiwi Jakarta to improve the efficiency and effectiveness of the training process. The system is designed to assist the HR department in managing training schedules, materials, and participant data, while also providing flexible learning access for employees. The development method used is the System Development Life Cycle (SDLC), which includes the stages of planning, analysis, design, implementation, testing, and maintenance. The test results show that the system functions properly and meets user needs. The implementation of UML diagrams, an intuitive user interface, and a structured database supports the smooth operation of the system in daily activities. Therefore, this application is expected to serve as an effective digital solution to support the continuous development of employee competencies.